2022
DOI: 10.3389/fenvs.2022.965925
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/Zn(OH)2 nanoparticles and self-cleaning coatings for the photocatalytic degradation of organic pollutants

Abstract: Zinc oxide (ZnO) nanostructures have emerged as efficient heterogeneous photocatalysts for the degradation of organic pollutants in aqueous solutions and industrial wastewaters. In this work, a simple and effective method is reported for the synthesis of zinc oxide/zinc hydroxide (ZnO/Zn(OH)2) hybrid nanoparticles using a mineral acid to enhance the photocatalytic activity of ZnO. Infrared spectroscopy reveals the presence of hydroxyl groups in ZnO/Zn(OH)2 nanoparticles. X-ray diffraction shows the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…It was noted that band gaps corresponding to the three edges observed in the UV-Vis spectrum with values of 2.80 eV, 3.44 eV, and 4.46 eV were calculated from the Tauc plot. These observations were in good agreement with studies reported by Ekennia et al [42] and Faheem et al [26]. These authors reported 2.72-4.37eV band gap in the case of biogenic ZnO nanostructures synthesized using Euphorbia sanguinea as the reducing agent.…”
Section: Results Anddiscussion 31 Characterizationssupporting
confidence: 92%
See 1 more Smart Citation
“…It was noted that band gaps corresponding to the three edges observed in the UV-Vis spectrum with values of 2.80 eV, 3.44 eV, and 4.46 eV were calculated from the Tauc plot. These observations were in good agreement with studies reported by Ekennia et al [42] and Faheem et al [26]. These authors reported 2.72-4.37eV band gap in the case of biogenic ZnO nanostructures synthesized using Euphorbia sanguinea as the reducing agent.…”
Section: Results Anddiscussion 31 Characterizationssupporting
confidence: 92%
“…Faheem et al recently reported a chemical method for producing ZnO/Zn(OH) 2 NPs via surface protonation of pre-synthesized ZnO NPs. Furthermore, when compared to bare ZnO NPs, ZnO/Zn(OH) 2 demonstrated a 3.5-fold improvement in photocatalytic efficiency for the degradation and removal of sunset yellow dye [26]. Furthermore, such ZnO/Zn(OH) 2 nanostructures can be used as a hard template to prepare a wide range of nanomaterials with diverse physicochemical properties, such as high specific surface area, crystallinity, and mesoporosity, thus exhibiting improved catalytic efficiency [27].…”
Section: Introductionmentioning
confidence: 99%
“…The optical band gap values of the obtained structures as a result of the aging of 2 and 6 h were found to be 3.59 and 2.89 eV for ZnO phase and 5.32 and 5.20 eV for Zn(OH) 2 phase, respectively. Band gap values of different solution‐aged samples in the UV–vis diffuse reflectance spectra of ZnO/Zn(OH) 2 composite NPs in Figure 5A are corresponded to Zn(OH) 2 phase, which is in good agreement in the literature 28 . As the solution aged, the band gap of the samples decreased.…”
Section: Resultssupporting
confidence: 88%
“…From the XRD results, it is clearly observed that the crystallite size decreases and the concentration of Zn(OH) 2 increases as the LA extract concentrations are increased. Firstly, the presence of Zn(OH) 2 can introduce an impurity level below the conduction band, which can act as scavengers of charge carriers enhancing the recombination time, 66 thus reducing the band gap. Moreover, the presence of surface hydroxyl group, facilitate the formation of non-covalent bond with the dye molecules.…”
Section: Resultsmentioning
confidence: 99%